2009
DOI: 10.1534/genetics.109.107219
|View full text |Cite
|
Sign up to set email alerts
|

Imprinting of the Y Chromosome Influences Dosage Compensation inroX1 roX2 Drosophila melanogaster

Abstract: Drosophila melanogaster males have a well-characterized regulatory system that increases X-linked gene expression. This essential process restores the balance between X-linked and autosomal gene products in males. A complex composed of the male-specific lethal (MSL) proteins and RNA is recruited to the body of transcribed X-linked genes where it modifies chromatin to increase expression. The RNA components of this complex, roX1 and roX2 (RNA on the X1, RNA on the X2), are functionally redundant. Males mutated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
37
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(38 citation statements)
references
References 41 publications
(45 reference statements)
1
37
0
Order By: Relevance
“…The enrichment of these motifs on the X chromosome is modest, suggesting that additional features contribute to X recognition [8]. Our prior studies led to the surprising conclusion that the siRNA pathway, and siRNA from a 1.688 X repeat, participated in X recognition [20, 21, 31]. Many of the 1.688 X repeats are transcribed and produce siRNA, making them attractive candidates for involvement in an siRNA-mediated process.…”
Section: Discussionmentioning
confidence: 99%
“…The enrichment of these motifs on the X chromosome is modest, suggesting that additional features contribute to X recognition [8]. Our prior studies led to the surprising conclusion that the siRNA pathway, and siRNA from a 1.688 X repeat, participated in X recognition [20, 21, 31]. Many of the 1.688 X repeats are transcribed and produce siRNA, making them attractive candidates for involvement in an siRNA-mediated process.…”
Section: Discussionmentioning
confidence: 99%
“…We previously reported that a maternally imprinted Y chromosome is a potent suppressor of roX1 roX2 lethality (Menon and Meller 2009). The expression of Y-linked protein-coding genes is restricted to the germline, making it unlikely that these genes influence the somatic process of dosage compensation.…”
mentioning
confidence: 99%
“…For example, the compound X-chromosome carried by the DX females is female-limited and could accumulate son-harming genetic variation, resulting in a female-biased sex ratio or reduced fitness of sons. Some evidence for this kind of effect has been presented and interpreted as resulting from imprinting of the Y-chromosome by the X in paternal transmission [12], [36]. Unfortunately we cannot test the latter two hypotheses directly since the Affymetrix chip only contains a handful of Y-linked transcripts, too few for statistical testing, and it is unknown which genes might be associated with SA zygotic drive.…”
Section: Discussionmentioning
confidence: 94%
“…Although there has been some theoretical treatment of this issue to date [28], [29], there is relatively little empirical data on the contribution of imprinting to the resolution of intralocus sexual conflict. The fruit fly Drosophila melanogaster is known both to experience substantial intralocus sexual conflict (at least in some laboratory populations) [1], [7], [8], [30], [31] and to exhibit genomic imprinting at certain loci [32][36]. However the contribution of genomic imprinting to the resolution of intralocus sexual conflict has, to our knowledge, never been empirically tested.…”
Section: Introductionmentioning
confidence: 99%